World Bank Guarantees for Oil and Gas Projects - Sinclair, Scott (World Bank, Washington, DC, 2012)
Private investors are considering several large-scale oil and gas production, pipeline, and cross-border pipeline projects in developing countries, including in West Africa and in the Caspian Sea region. While the World Bank and the International Monetary Fund are well known for their work in helping to create enabling environments for foreign investment in large infrastructure projects, by supporting reform in such areas as taxation and energy legislation, this Note focuses on a different role for the World Bank -- encouraging private sector involvement in large-scale oil and gas projects by providing guarantees in direct support of the government contractual undertakings that may be needed to induce foreign direct investment in these projects. World Bank guarantees offer a unique type of risk mitigation that may prove to be a catalyst in raising finance for these projects.